Protective effect of different anti-rabies virus VHH constructs against rabies disease in mice. - Sanne Terryn; Aurélie Francart; Sophie Lamoral; Anna Hultberg; Heidi Rommelaere; Angela Wittelsberger; Filip Callewaert; Thomas Stohr; Kris Meerschaert; Ingrid Ottevaere; Catelijne Stortelers; Peter Vanlandschoot; et al. (PLoS ONE, 2014)
Rabies virus causes lethal brain infection in about 61000 people per year. Each year, tens of thousands of people receive anti-rabies prophylaxis with plasma-derived immunoglobulins and vaccine soon after exposure. Anti-rabies immunoglobulins are however expensive and have limited availability. VHH are the smallest antigen-binding functional fragments of camelid heavy chain antibodies, also called Nanobodies. The therapeutic potential of anti-rabies VHH was examined in a mouse model using intranasal challenge with a lethal dose of rabies virus. Anti-rabies VHH were administered directly into the brain or systemically, by intraperitoneal injection, 24 hours after virus challenge. Anti-rabies VHH were able to significantly prolong survival or even completely rescue mice from disease. The therapeutic effect depended on the dose, affinity and brain and plasma half-life of the VHH construct. Increasing the affinity by combining two VHH with a glycine-serine linker into bivalent or biparatopic constructs, increased the neutralizing potency to the picomolar range. Upon direct intracerebral administration, a dose as low as 33 µg of the biparatopic Rab-E8/H7 was still able to establish an anti-rabies effect. The effect of systemic treatment was significantly improved by increasing the half-life of Rab-E8/H7 through linkage with a third VHH targeted against albumin. Intraperitoneal treatment with 1.5 mg (2505 IU, 1 ml) of anti-albumin Rab-E8/H7 prolonged the median survival time from 9 to 15 days and completely rescued 43% of mice. For comparison, intraperitoneal treatment with the highest available dose of human anti-rabies immunoglobulins (65 mg, 111 IU, 1 ml) only prolonged survival by 2 days, without rescue. Overall, the therapeutic benefit seemed well correlated with the time of brain exposure and the plasma half-life of the used VHH construct. These results, together with the ease-of-production and superior thermal stability, render anti-rabies VHH into valuable candidates for development of alternative post exposure treatment drugs against rabies.